2021
DOI: 10.1177/0885066621996257
|View full text |Cite
|
Sign up to set email alerts
|

Sepsis Mortality Is high in Patients With Connective Tissue Diseases Admitted to the Intensive Care Unit (ICU)

Abstract: Objectives: Patients with connective tissue diseases (CTD) such as systemic lupus erythematosus (SLE) have an increased risk for infections. This study investigated the outcome and characteristics of CTD patients under intensive care unit (ICU) treatment for sepsis. Methods: A single-center retrospective analysis was conducted and reviewed all patients with a CTD diagnosis admitted to the ICU of a university hospital for sepsis between 2006 and 2019. Mortality was computed and multivariate logistic regression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 44 publications
2
7
0
Order By: Relevance
“…Moreover, within the repeated group, scores of the tools were higher during the last ICU stays in the comparison between the first admissions and the last ones (all P < 0.05), suggesting that sepsis developing repeatedly were more severely ill than those occurred at the first time. These findings are partly similar to other published literature reporting a correlation between Max SOFA, CCI, and SAPS-II scores and ADs [ 5 , 29 31 ]. To summarize, the higher scores of three quantified assessment tools were long-term mortality-associated risk factors for AD patients whether with recurrent sepsis episodes or with single one.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Moreover, within the repeated group, scores of the tools were higher during the last ICU stays in the comparison between the first admissions and the last ones (all P < 0.05), suggesting that sepsis developing repeatedly were more severely ill than those occurred at the first time. These findings are partly similar to other published literature reporting a correlation between Max SOFA, CCI, and SAPS-II scores and ADs [ 5 , 29 31 ]. To summarize, the higher scores of three quantified assessment tools were long-term mortality-associated risk factors for AD patients whether with recurrent sepsis episodes or with single one.…”
Section: Discussionsupporting
confidence: 92%
“…Whereas, these studies on repeated sepsis rarely involved AD population. Other studies on ADs found that sepsis was an important factor influencing the mortality of ADs patients [ 5 , 20 ], but they did not give a specific definition of whether the sepsis they studied was new-onset or recurrent. These studies provided some clues of the impact of sepsis on ADs, and our findings regarding the long-term prognosis of ADs in relation to recurrent sepsis helps made up for the limitations of these studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SAPS II scores were also observed to be higher among non-survivors in all three assessments, but statistical significance was not reached for the comparison of admission scores between the groups. In a study examining the mortality characteristics of sepsis patients hospitalized in the intensive care unit, Krasselt et al suggested that -similar to our study-SOFA, SAPS II and APACHE II scores could be used to predict mortality [4]. Haas et al reported that these 3 scales were successful in predicting mortality in sepsis, but, interestingly, quick SOFA (qSOFA) had better results than SOFA, SAPS II and APACHE II [5].…”
Section: Discussionsupporting
confidence: 75%
“…Different scoring systems have been used for the assessment of sepsis severity, prediction of mortality and morbidity, and determination of prognosis in the intensive care unit. Researchers have examined the utility of these scores and additional parameters in predicting mortality among patients with sepsis in many studies, which have resulted in the publication of various findings contributing to the guidelines of sepsis management [4][5][6][7][8][9][10][11]. In Turkey however, there are only a few studies examining outcomes associated with the clinical practice of the international guidelines for the management of severe sepsis and septic shock.…”
Section: Introductionmentioning
confidence: 99%